ENGINEERING GEOLOGICAL INVESTIGATION OF SLOPE FAILURES IN PALEO MIKROHORIO EVRYTANIA PR., AIMING AT ITS SAFE RESIDENTIAL DEVELOPMENT - Ρόζος Δ.; Αποστολίδης E. (Bulletin of the Geological Society of Greece, 2004)
The geological structure and tectonism of Paleo Mikro Horio development area in relation with the morphology and engineering geological - hydrogeological behaviour of the formations contributed to the instability of certain slopes and the manifestation of serious landslides, with distinctive event, the landslides manifested on 13/1/1963, that resulted in the death of 13 persons and the destruction of the greatest part of the village. Manifestation of recent phenomena refers to slope failures restricted and surficial, outside the residential area at the upward forest slope of the village. To ensure safe delimitation of the village residential development area, all the abovementioned data were evaluated, taking also into account the rather high seismic risk of the area, and an engineering geological map was compiled at a scale of 1:5.000. This map includes seven (7) engineering geological units, three (3) for the basement formations and four (4) for the recent formations. For every one of them a general description, the engineering geological and hydrogeological behaviour as well as basic approaches of the engineering geological setting resulting from the geodynamic-geomorphologic evolution of the area are given. Based on all the collected data and the engineering geological map, recommendations relevant for the residential use development of the area were formulated, mainly by means of a zonation map including three zones as following: (a) areas considered safe without taking specific additional measures, (b) areas considered insecure due to the activity of the groundwater and their instability in general, specifically under dynamic load, although current soil displacement phenomena have not been observed and (c) areas covered by the 1963’s landslide materials, considered unsuitable for building. Finally, the application of measures that improved the geotechnical conditions of the new residential areas as well as the existed ones was thought to be necessary, apart from the good foundation of the houses and the anti-seismic enforcement of the constructions.